The Effect of Safety Leadership on Safety Participation of Employee: A Meta-Analysis - Zhao, Linyi; Yang, Daojian; Liu, Suxia; Nkrumah, Edmund Nana Kwame (Frontiers in Psychology, 2022)
Recently, the promotion of safety participation has become a hot spot in behavioral safety research and safety management practice. To explore the relationship between safety leadership and safety participation, a theoretical model was established and 33 articles (35 independent samples) in work safety from 2000 to 2021 were selected for a meta-analysis. By evaluating the impact of safety leadership, which incorporates transformational, transactional, and passive leadership styles, on work safety. The results show that safety leadership has a positive impact on both safety climate and safety participation. Both safety transactional leadership and safety transformational leadership positively impact safety participation, and the impact of safety transformational leadership is greater, while safety passive leadership has no impact on safety participation. The study as well establishes that safety climate plays a partial mediating role between transformational safety leadership and employee safety participation. Under the condition of developed economic level or high-risk industry, safety leadership indicated a greater influence on safety participation. Hence, it is recommended that when enhancing the safety participation of employees, the influence of the macro environment and safety climate should not be undermined.